Critical Incidents for Teachers’ Professional Development - Joshi, Khem Raj (Journal of NELTA Surkhet, 2018)
Analysis of critical incidents is one of the approaches of teacher professional development. A critical incident is any unplanned event which takes place during the class. It is something we interpret as a problem or challenge in a particular context, rather than a routine occurrence. The incident is said to be critical because it is valuable and has some meaning. In other words, incidents happen but critical incidents are created because of their importance. Teachers can critically analyze any of their lessons and can make a particular event critical by reflecting on it. The teachers ask not only what happened but also why it happened. They then use the incidents for future reference. This article deals with the benefits of critical incidents and the ways to analyze them, which lead to successful teacher professional development. Journal of NELTA Surkhet, Vol. 5 January, 2018f, Page: 82-88